Pengaruh Modal Intelektual Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variable Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Sihite, Rukiah Natasya; Silaban , Adanan; Harefa, Melinda Stefani (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This study aims to determine the effect of intellectual capital on firm value, with financial performance as an intervening variable, in manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2022 period. The independent variable in this study is intellectual capital measured using Value Added Physical Capital (VACA), while the dependent variable is firm value proxied by Price Book Value (PBV). Financial performance functions as an intervening variable measured by Return On Asset (ROA). This type of research is associative causal, with a population covering all manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling, where from a total population of 63 companies, a sample of 31 companies was obtained. The data analysis method applied is path analysis. The results of the data analysis show that individually, intellectual capital has a positive effect on financial performance. However, intellectual capital does not have a direct positive effect on firm value. Conversely, intellectual capital has an indirect positive effect on firm value through the mediation of financial performance. The results of the goodness of fit model test show that the regression model used is able to predict the company's value, as evidenced by the F significance value of 0.007. The adjusted R-Square value of 0.125 indicates that the independent variable can explain the variation in the dependent variable by 12.5%, while the remaining 87.5% remains significant.